Ensino de geometria e perspectiva: um olhar pelas fotografias - Silva, Lenise Júlia Fassini da (2018)
This research brings elements of Projective Geometry to a classroom of the 3rd year of High School, through photographs and art. For this, we present a historical report since the 5th postulate of Euclides and its most varied attempts made for anothers mathematicians to show this unsucessfully, passing for criations of new geometric concepts, until come on the actual days with the formalization of these geometries. We also look at official documents about the teaching of a new geometry in the basic education of the state of Espírito Santo (ES). We applied the didactic sequence in an ES state school and analyzed the impacts on the students’ learning, concluding that the classroom discussion and the students' own artistic production may have facilitated the understanding of the mathematical topics worked in the classes.